2018
DOI: 10.22159/ajpcr.2018.v11i11.27463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antifungal Potential of Allium Ampeloprasum Against Fungal Phytopathogens

Abstract: Objective: Present study evaluates the antifungal potential of Allium ampeloprasum extracts against two phytopathogens of economic importance, namely Alternaria triticina and Magnaporthe oryzae which are found to be one of the greatest threats to wheat and rice crop worldwide.Methods: Four different organic solvents, i.e., water, methanol, acetone, and hexane were used for extract preparation based on the increasing order of polarity. Further, different concentrations of these extracts were used to perform a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…The results obtained with Cynbopogon citratus extracts were in accordance with those obtained by [12] [24] who showed that these extracts had antifungal activities on the development of Colletotrichum kahawae responsible for anthracnose of coffee berry and Colletotrichum musae and Aspergillus niger responsible for banana fruit rot respectively. Similarly, those obtained with Allium ampeloprasum extract are similar to the results obtained by [25] who showed that the A. sativum and A. ampeloprasum extracts inhibited the development of Alternaria triticina, causal agent of leaf blight in wheat and Magnaporthe oryzae, causal agent of blast disease in rice.…”
Section: Effect Of Plant Extracts On the Radial Growth Fungal Pathogenssupporting
confidence: 87%
See 1 more Smart Citation
“…The results obtained with Cynbopogon citratus extracts were in accordance with those obtained by [12] [24] who showed that these extracts had antifungal activities on the development of Colletotrichum kahawae responsible for anthracnose of coffee berry and Colletotrichum musae and Aspergillus niger responsible for banana fruit rot respectively. Similarly, those obtained with Allium ampeloprasum extract are similar to the results obtained by [25] who showed that the A. sativum and A. ampeloprasum extracts inhibited the development of Alternaria triticina, causal agent of leaf blight in wheat and Magnaporthe oryzae, causal agent of blast disease in rice.…”
Section: Effect Of Plant Extracts On the Radial Growth Fungal Pathogenssupporting
confidence: 87%
“…In addition, the results are also similar to those of [28], reported that Cupressus lusitanica extracts had fungistatic activity on the growth of Phytophtora colocasiae, the agent responsible for taro blight. The fungitoxicity of Cymbopogon citratus extract on the growth of the pathogens was in accordance with that of [25], who showed the fungitoxicity activity of these extracts on the development of Alternaria triticina, causal agent of leaf blight in wheat.…”
Section: Effect Of Plant Extracts On the Radial Growth Fungal Pathogenssupporting
confidence: 86%